ASSESSING PHARMACEUTICAL CARE NEEDS OF PAEDIATRIC IN-PATIENTS: A TEAM BASED APPROACH. Issue 9 (17th August 2016) - Mott, Adele; Kafka, Susan; Sutherland, Adam
Abstract : Aims: To pilot a novel approach to providing pharmaceutical care to paediatric inpatients using structured referral and assessment tools. Using standardised referral criteria to ensure patients are assessed by appropriately skilled pharmacists. Method: Three wards of varying acuity and specialism were selected in a tertiary children's hospital in England - General Paediatric Ward (GPW), High Dependency Unit (HDU) and Haematology/Oncology Ward (HOW). The project ran for three months. Three levels of pharmacist were involved: Band 8 ("Level 3"), Paediatric Band 7 ("Level 2") and rotational band 6/7 ("Level 1"). All patients were initially triaged by an appropriate pharmacist using criteria: Early Warning Scores (EWS), reason for admission, Level 1 Medicines Reconciliation. Patients were then graded according to level of acuity: Level 1: EWS 0–2 AND no significant medication history; Level 2: EWS 2–4 OR significant medication history; level 3: EWS >4. After initial triage patients were handed over using SBAR1 in a structured group "huddle", and acuity levels validated. Pharmaceutical care plans were formulated and patients allocated to appropriate pharmacists. On the GPW patients were triaged by a level 3 pharmacist ("Refer Down") for the first 2 weeks. On review of data generated and acuity levels triage was changed to be carried out by a level 1 pharmacist ("Refer Up.") In the HDU and HOW the Refer Down system was used. All patients in the pilot were reassessed and acuity re-evaluated daily ensuring appropriate pharmacist review. Data was collected on initial acuity level and any change in level following the huddle; (1) to identify those patients in need of a higher level of pharmaceutical input; (2) to identify the level of pharmacist most appropriate to a given clinical area. Results: 245 patients were assessed. 148 (83%) patients on GPW were triaged as level 1. Using a "refer down" model there was no change in patient acuity. Using "refer up" only 5 patients were reclassified to a higher level of care post-huddle. 18 (64%) patients in HOW were triaged as level 3. Eight patients were reduced to level 2 after the huddle. 53% of patients were classified as level 2 post-huddle. There were very few level 1 patients in HOW. PHDU demonstrated similar demographics, though with more level 1 patients. Conclusion: This study demonstrates the potential benefits of a team based approach in optimising pharmaceutical care by directing patients to the most appropriate pharmacist. The huddle facilitates clinical supervision of patients and pharmacists. There may be benefits in efficiency using this system in a resource-constrained environment. This study does not present longitudinal changes in acuity. More research is needed.